Ultrasonic extraction of flax polysaccharides - V. G. Zadorozhny; L. D. Chulak; Yu. L. Chulak; O. L. Chulak; I. I. Yanchak (Kazimierz Wielki University, 2017)
To date, flax is one of the most promising crops that are dynamically developing. The demand for flax and products of its processing in Ukraine and other countries is due to increased interest in its use in medicine, cooking and cosmetology [1]. The main nutrients that determine the biological activity of flaxseed are protein substances, vitamins, enzymes, carbohydrates and fatty oils, which include glycerides of linoleic (35-45%), linoleic (25-35%), oleinic (15-20% ), stearic acid (8-9%). In our time, from flax seeds on an industrial scale only oil is obtained, using one of the traditional mechanical methods. According to the biological value, oil from flaxseed oil occupies the first place among other edible vegetable oils and contains a lot of substances useful for the body (polyunsaturated acids, vitamins F, A, E, K, saturated fatty acids (10% composition). Flaxseed oil is excellent a source of valuable polyunsaturated fatty acids ω-3 and ω-6 (the human body can not independently synthesize these valuable acids). The aim of the work is to study the methods of obtaining and application of flax polysaccharides, as well as the development of energy-efficient technology for their obtaining. The conducted researches have shown, that at application of ultrasonic processing in the process of extraction of flax polysaccharides the extraction time is significantly reduced. The maximum yield of polysaccharides takes place with ultrasound processing of extraction capacity of 70 W / m2 for 20 minutes. The flax polysaccharides obtained in this way can be successfully used as antioxidant, bactericidal, fungicidal and antiviral drugs.